2009
DOI: 10.1007/s10886-009-9712-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Defensive Volatiles of the Forked Fungus Beetle, Bolitotherus cornutus, Living on Two Species of Fungus

Abstract: Forked fungus beetles, Bolitotherus cornutus, feed, mate, and live on the brackets of several species of shelf fungus that grow on decaying logs. In response to the specific threat stimulus of mammalian breath, B. cornutus beetles produce a volatile defensive secretion. We tested beetles collected from different host fungi to determine whether defensive secretion blends varied with host type. Using solid phase microextraction and gas chromatographymass spectrometry, we detected large amounts of the alkylated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…However, at least some of the negative correlations with 3-methylphenol may be artifacts; when the relative peak area of 3-methylphenol is close to 100%, addition of a small percentage of another alkylphenol must perforce diminish the value for 3-methylphenol and create a negative association. Unlike the negative correlation we observed between 3-methylphenol and 3-ethylphenol in C. cordicollis, these compounds are positively correlated in the tenebrionid beetle Bolitotherus cornutus (Panzer) (Holliday et al, 2009).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…However, at least some of the negative correlations with 3-methylphenol may be artifacts; when the relative peak area of 3-methylphenol is close to 100%, addition of a small percentage of another alkylphenol must perforce diminish the value for 3-methylphenol and create a negative association. Unlike the negative correlation we observed between 3-methylphenol and 3-ethylphenol in C. cordicollis, these compounds are positively correlated in the tenebrionid beetle Bolitotherus cornutus (Panzer) (Holliday et al, 2009).…”
Section: Discussioncontrasting
confidence: 94%
“…However, they, like we, cannot disprove the hypothesis that geographic variation in defensive secretions is attributable to different precursors in food consumed by insects in the field. For example, the composition of defensive secretions of fungusfeeding tenebrionid beetles is food-dependent (Holliday et al, 2009), and the seasonal variation in defensive secretions in a predatory dytiscid beetle may reflect the availability of plantsynthesized precursors acquired by herbivore prey (Miller and Mumma, 1974). The assemblage of insects available for C. cordicollis to scavenge no doubt differs between the banks of the Delaware River and the beaches of Lake Winnipeg, and we expect the available dietary precursors of phenolic compounds to differ between our source localities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that quinones including p -benzoquinone and its derivatives are found in some beetles (Coleoptera) [22][24] and p -benzoquinone is a metabolite produced by the oxidation of 1,4-hydroquinone [25]. Because p -benzoquinone shows high toxicity to living organisms, the concentration of p -benzoquinone was 10-fold lower than that of 1,4-hydroquinone in our injection experiments.…”
Section: Discussionmentioning
confidence: 78%
“…Eisner and co-workers reported that benzoquinone 9 and phenol 21 from Zygopachylus albimarginis (Manaosbiidae) [6] had the same biosynthetic origin for both components. The production of benzoquinones, hydroquinones and phenols by the forked fungus beetle Bolitotherus cornutus also suggests that the alkyl benzoquinones and alkyl phenols might share a similar biosynthetic origin [36]. Scheme 2.…”
mentioning
confidence: 99%